2018
DOI: 10.1101/304196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential requirements of tubulin genes in mammalian forebrain development

Abstract: KEY WORDSTubulin human forebrain development ABSTRACT Tubulin genes encode a series of homologous proteins used to construct microtubules which are essential for multiple cellular processes. Neural development is particularly reliant on functional microtubule structures. Tubulin genes comprise a large family of genes with very high sequence similarity between multiple family members. Human genetics has demonstrated that a large spectrum of cortical malformations results from de novo heterozygous mutations in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…Using real-time PCR experiments, Breuss and colleagues have demonstrated lower expression of tubb2a during brain development, which reached its highest level at E14.5, E16.5, and around the time of birth [ 78 ]. This finding suggests that this tubulin carries out relatively minor functions during brain development, in accordance with the mild brain phenotypes observed in patients harboring TUBB2A mutations [ 91 , 92 , 93 ] and the recent finding that the loss of tubb2a leads to relatively mild cortical malformations in mice [ 10 ]. Accordingly, we have recently described a novel TUBB2A mutation associated with a phenotype presenting peripheral sensory motor polyneuropathy without cortical malformation [ 94 ].…”
Section: Neuronal Microtubules: Regulative Mechanismssupporting
confidence: 83%
See 2 more Smart Citations
“…Using real-time PCR experiments, Breuss and colleagues have demonstrated lower expression of tubb2a during brain development, which reached its highest level at E14.5, E16.5, and around the time of birth [ 78 ]. This finding suggests that this tubulin carries out relatively minor functions during brain development, in accordance with the mild brain phenotypes observed in patients harboring TUBB2A mutations [ 91 , 92 , 93 ] and the recent finding that the loss of tubb2a leads to relatively mild cortical malformations in mice [ 10 ]. Accordingly, we have recently described a novel TUBB2A mutation associated with a phenotype presenting peripheral sensory motor polyneuropathy without cortical malformation [ 94 ].…”
Section: Neuronal Microtubules: Regulative Mechanismssupporting
confidence: 83%
“…In many organisms, both α and β tubulins are encoded by multiple genes at different loci [ 8 , 9 ]. Most of them, such TUBB2A , TUBB2B , and TUBA1A , TUBA1B , TUBA1C , are clustered in the genome and are presumably the products of genomic duplications [ 10 ]. In vitro experiments have shown that tubulin isotypes have different effects on MT dynamics [ 11 , 12 , 13 , 14 ], suggesting that they can differentially regulate the MT network in vivo.…”
Section: Microtubule Structural and Functional Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Insight to mechanistic questions can be gained from examining available mammalian models of Tuba1a mutations. Homozygous Tuba1a deletion results in severe brain defects including disruption of cortical layering, enlargement of cerebral and third ventricles, and a reduction in the size of the basal ganglia (Bittermann et al, ). In contrast, no brain defects were noted in heterozygous Tuba1a knock‐out mice (Bittermann et al, ).…”
Section: Mouse Models Provide Insight Into Tubulinopathy‐associated Mmentioning
confidence: 99%
“…To overcome the technical limitations to studying the specific impact of TUBA1A in adult 76 neurons, we use the Tuba1a ND mutant mouse which harbors an asparagine to aspartic acid substitution at 77 amino acid residue 102 (Gartz Hanson et al, 2016). Homozygous Tuba1a ND/ND mice are neonatal lethal 78 and have severe brain malformations consistent with homozygous Tuba1a null and Tuba1a quas mutant mice 79 (Bittermann et al, 2019) and similar to phenotypes observed in human patients with heterozygous 80 TUBA1A mutations (Aiken et al, 2017;Gartz Hanson et al, 2016). The corresponding ND substitution in 81 the primary -tubulin in yeast decreased -tubulin protein levels, altered microtubule dynamics, reduced 82 incorporation of the mutant -tubulin into the lattice, and impaired mitotic division (Gartz Hanson et al, 83 2016).…”
Section: Introduction 46mentioning
confidence: 99%